Subsídios para atenção integral do idoso: perfil do usuário em uma UBS de Franca (SP) - Horta, Heloisa Helena Lemos (2007)
The aging of the human being population is a worldwide phenomenon and according to statistics projections of the World Health Organization, in 2025, Brazil could reach 32 million people with 60 years old or more, getting the 6th place related to the number of elderly people. Considering that Brazil is not prepared to receive this elderly population and knowing that the new Brazilian legislation ensures government actions which preserve the living conditions improvement of them, this study aims to identify the profile of elderly people in a UBS, Franca city (SP), addressing their full medical attendance, which the theoretical support is the aging of the population. It is a field descriptivequantitative research, performed during March 2007 with 30 elders, being 20 women and 10 men, whose aged between 60 and 87 years old. It was conducted through interviews with a personal questions instrument including issues relating to the topic. The data were presented in absolute and percentual values and the results allow us to consider that a low socio-economic level, lack of information and ignorance of the rights of the elderly difficult their access to full attention as provided in the existing legislation.